2021
DOI: 10.11152/mu-2982
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic ultrasonography for assessing the nerve-fasciae relationship in entrapment syndromes

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Indeed, with US, it is possible to demonstrate the thickening of a fascial layer, the changing of its echogenicity, and to analyze the relationships between fasciae, nerves, and vessels. According to some studies [ 11 , 12 ], it is also possible to investigate the gliding between muscles and the adjacent fascial layers, and between the various fascial layers, that seem to be related to myofascial pain. A review by Fede et al [ 13 ] reported that the ultrasound data collected for the same fascia differed depending on the ultrasonographer, probe position, and/or intra-individual anatomic variability.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, with US, it is possible to demonstrate the thickening of a fascial layer, the changing of its echogenicity, and to analyze the relationships between fasciae, nerves, and vessels. According to some studies [ 11 , 12 ], it is also possible to investigate the gliding between muscles and the adjacent fascial layers, and between the various fascial layers, that seem to be related to myofascial pain. A review by Fede et al [ 13 ] reported that the ultrasound data collected for the same fascia differed depending on the ultrasonographer, probe position, and/or intra-individual anatomic variability.…”
Section: Introductionmentioning
confidence: 99%